To Celebrate and to Contemplate: the Religious and the Tragic in Greek Myth - Azevedo, Cristiane A. de (2015)
In Greek myth, the religious is revealed through the proximity between men and gods, through the being together contemplating the divine actions at the festive banquet and being contemplated by the gods. Following the path opened by philologist and helenist Karl Kerényi, this article aims at thinking this paradoxical relationship as being able to reveal the religious and the tragic. The author points out a privileged element to perceive the presence of the religious and the tragic in Greek myth: the laugh of the gods.